Kelayakan Usaha UMKM dengan Pendekatan Finansial - Dedi nur yusuf; Siti Nur Qomariyah (Program Studi Agribisnis, 2021)
A business can be said to be achieve if it fulfills several criteria. Therefore, a study is needed to determine whether or not a business is suitable. One of the potential businesses was ornamental plants. Thus, this study aims to determine the income and feasibility in terms of R/C ratio of the ornamental plant business at Brother Farming. This research was conducted in April 2021 at Sukotirto, Badang Village, Ngoro, Jombang, East Java. Purposive sampling method was used as a method with the consideration that Brother Farming is an ornamental plant business that produces and manages ornamental plants independently. It was located in Badang, Ngoro, Jombang, East Java. The data analysis used in this research includes cost analysis, revenue analysis, income, and R/C ratio. This research obtained primary data, namely interview and documentation. Interview were conducted with business owner and workers. The results of this study indicates that the income earned in 2019 was Rp. 73.667.900 while in 2020 it was Rp. 97.676.900.Therefore, the value of business feasibility of the R/C Ratio obtained in 2019 was 1,83 and 2,51 in 2020. As a result, the R/C ratio showed a number > 1, which means that the ornamental plant business at Brother Farming profitable and suitable to be developed.